Heterogeneity of Pre-diabetes and Type 2 Diabetes: Implications for Prediction, Prevention and Treatment Responsiveness - Faerch, Kristine; Hulman, Adam; P.J. Solomon, Thomas (Current Diabetes Reviews, 2016)
Type 2 diabetes is a heterogeneous disease with large variation in the relative contributions of insulin resistance and beta cell dysfunction between subgroups and individuals. Some of these differences are reflected in the way people are diagnosed. However, differences in glucose regulation exist among individuals even in those with comparable diagnostic glucose levels. In this review we address the heterogeneity of pre-diabetes and type 2 diabetes with special emphasis on differences in the pathophysiology and treatment responses related to the diagnostic criteria. We also discuss whether novel glycaemic markers of diabetes risk can provide additional information to the established diagnostic criteria. A better understanding of the underlying mechanisms responsible for elevated fasting versus postprandial glucose concentration, as well as knowledge about the expected responsiveness to treatment in individuals with different clinical characteristics at diagnosis, may contribute to optimising strategies for management of hyperglycaemia in both pre-diabetes and type 2 diabetes.
Keywords: insulin resistance